Pattern of Mortality in Peritonitis Patients with different Mannheim Peritonitis Index Categories - Bano, Sania; Allah Nawaz; Ahmad, Naeem; Hassan, Ahmad; Noor, Ammara; Nawaz, Khurram (Indus Journal of Bioscience Research, 2025)
Background: Peritonitis caused by hollow viscus perforation is a frequent surgical emergency. Every surgeon has the task of accurately diagnosing and managing this condition. This resulted in the creation of illness severity grading systems that would help with care and accurately forecast future outcomes. Objective: To evaluate Mannheim Peritonitis Index in predicting the mortality among patients with peritonitis and to determine the pattern of mortality in peritonitis patients with different MPI categories. Methodology: This descriptive case series was conducted in department of General Surgery, Doctor Faisal Masood Teaching Hospital, Sargodha. 140 individuals with peritonitis due to hollow viscus perforation were assessed. MPI was measured upon admission and patients were divided into three groups depending on their MPI scores. The mortality rate was computed for each group. The data is analyzed with SPSS version 25.0. The Chi-square test is used to compare results. A P value of less than 0.05 is deemed statistically significant. Results: The mean age of patients was 41.94 ± 10.43 years with male majority (72.2%). Site of perforation in 26.8% patients was appendix followed by ilium in 20.6%, stomach in 16.5%, duodenum in 15.5%. Mean MPI score in our study was 23.31± 8.31. There were eighteen deaths (12.9%) in our study. The rate of mortality was 10(7.1%) patients in category III and compared to 8(5.7%) and 0% in patient category II and category I. Conclusion: MPI scoring system accurately predicts morbidity and death in individuals with peritonitis. The MPI scoring system is a simple and effective technique for assessing such individuals, and it may be used to guide patient treatment decisions after the ultimate operation is completed. It aids in the identification of high-risk patients.